Starting a Nonprofit at Your Church - Skjegstad, Joy (Rowman & Littlefield Publishers, 2002)
A large and growing number of congregations are setting up church-based nonprofit organizations in order to operate community development or educational programs. Once formed, the nonprofit structure allows for new opportunities for accessing additional funding and drawing new collaborative partners and volunteers into the ministry. Joy Skjegstad outlines the step-by-step procedures for setting up a 501(c)3 nonprofit organization connected to a congregation using simple, easy-to-understand terminology and plenty of examples from churches that have already taken on this task. Whether a congregation is setting up new program or has an established nonprofit that needs to be restructured or redefined, congregations will find helpful guidance in this practical, experience-based book.